AN ANALYSIS OF TOEIC TEST PREP APPLICATION ON THE STUDENT’S LISTENING COMPREHENSION AT STATE POLYTECHNIQUE OF BENGKALIS - Pretti Ristra; Agnes Arum Budiana; Aswandi Aswandi (Politeknik Negeri Bengkalis, 2023)
In the era of industry 4.0, most of human’s activities cannot be separated from digitalization. The digitalization has collaborated with the educational institution. The Language Centre of Politeknik Negeri Bengkalis usually holds a TOEIC test (online and offline) to fulfill the industrial world in preparing qualified alumni. The TOEIC instructor or lecturer used a TOEIC application while teaching in TOEIC intensive class where it is a preparation class for the students. This study investigated the problem faced by the students during listening through application which is called TOEIC Test Prep in learning TOEIC materials in the TOEIC intensive class and also investigated the challenges faced by them during the use of application. The participants of the study were 43 non-English majoring students (the fifth semester) of State Polytechnique of Bengkalis. The study used questionnaires to collect the data and the data were analyzed based on three categories; students’ background, the general difficulties on TOEIC listening, the challenges during listening through the use of TOEIC Test Prep application. The result of the study showed that the non-English majoring students in Politeknik Negeri Bengkalis felt the application had helped them in listening practice. Key words: TOEIC, TOEIC Test Prep Application, Listening Comprehension